Genetic characterization of the partial mitochondrial cytochrome oxidase c subunit I (cox 1) gene of the zoonotic parasitic nematode, Ancylostoma ceylanicum from humans, dogs and cats - Romano, Ngui; Mohammed A.K, Mahdy; Kek, Heng Chua; Rebecca, Traub; Yvonne Ai, Lian Lim (Elsevier Science, Ltd., 2013)
Ancylostoma ceylanicum is the only zoonotic hookworm species that is able to produce patent infections in humans with the majority of cases reported in South East Asia. Over the pastfew years,there have been an increasing number of studies investigating the prevalence of this parasitic zoonosis using molecular diagnostic tools and a single genetic locus as marker for species identification. As there can be limitations in using a single genetic locus for epidemiological studies and genetic discrimination, the complementary use of a more variable locus will provide additional evidence to support the zoonotic exchange of hookworm species between humans and animals. In the present study, the cytochrome c oxidase subunit 1 (cox 1) sequence of A. ceylanicum from positive human and animal fecal samples were determined and compared with published reference sequences. Phylogenetic analysis demonstrated that isolates of A. ceylanicum were divided into two clusters, one consisting 3 human isolates and the other comprising 19 isolates of human and animal origin from different geographical locations within Malaysia. The two groups of A. ceylanicum could be distinguished from one another through five fixed nucleotide differences at locations 891, 966, 1008, 1077 and 1083. The detection of genetically distinct groups and considerable level of genetic variation within the cox 1 sequence of A. ceylanicum might suggest potential haplotypelinked differences in zoonotic, epidemiological and pathobiological characteristics, a hypothesis that still needs further investigation.